Auditory attention causes gain enhancement and frequency sharpening at successive stages of cortical processing: evidence from human EEG - de Boer, Jessica; Krumbholz, Katrin (Massachusetts Institute of Technology Press, 2018)
Previous findings have suggested that auditory attention causes not only enhancement in neural processing gain, but also sharpening in neural frequency tuning in human auditory cortex. The current study was aimed to reexamine these findings, and investigate whether attentional gain enhancement and frequency sharpening emerge at the same or different processing levels, and whether they represent independent or cooperative effects. For that, we examined the pattern of attentional modulation effects on early, sensory-driven cortical auditory-evoked potentials (CAEPs) occurring at different latencies. Attention was manipulated using a dichotic listening task and was thus not selectively directed to specific frequency values. Possible attention-related changes in frequency tuning selectivity were measured with an EEG adaptation paradigm. Our results show marked disparities in attention effects between the earlier N1 CAEP deflection and the subsequent P2 deflection, with the N1 showing a strong gain enhancement effect, but no sharpening, and the P2 showing clear evidence of sharpening, but no independent gain effect. They suggest that gain enhancement and frequency sharpening represent successive stages of a cooperative attentional modulation mechanism, which appears to increase the representational bandwidth of attended versus unattended sounds.